Hubungan Antara Kadar Hemoglobin Ibu Menyusui dan Kadar Zat Besi dalam Air Susu Ibu 6 Bulan Postpartum - Siti Helmyati, Hamm Hadi (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Iron deficiency is considerend to be the most important etiology of ane-mia in pregnant and lactating women. In population where exclusive breastfeeding is prevalent iron status of the baby is dependent on iron intake from the breastmilk, Whether breastmilk iron content is associated with maternal hemoglobin concentration at 6 mo postpartum is unknown.Objective of the study: the study was conducted to assess the association between maternal's hemoglobin concentration at 4 and 6 month postpartum with iron content in breastmilk at 6 month postpartum.Study Design: Hemoglobin concentration of 158 lactating women participated in the Bantu! Anemia and Pregnancy Outcome (BANPO) was assessed at 6 mo postpartum using Cyanmethemoglobin method. Fifty five (34.8%) of them were found to be anemic at 4 mo postpartum and 103 (65.2%) were not anemic. Iron content in the breastmilk was assessed by using atomic absorption spectrophotometer (AAS) method.Results:result of this study showed that breastmilk iron content was significantly as-sociated with maternal hemoglobin concentration. Every one unit increase in hemo-globin concentration was associated with 0.098 unit increase in breastmilk iron con-tent (p=0.058),Conclusions: Breast milk iron content is associated with maternal hemoglobin con-centration at 6 month postpartum. Keywords: infant, maternal, anaemia, iron, breastmilk